Books, Blackboards, and Bullets: School Shootings and Violence in America - Lebrun, Marcel (Rowman & Littlefield Publishers, 2008)
The sad fact is that many youths and children do not feel safe either at school or at home. In recent years, there have been increases in bullying, teacher assault, and student-to-student physical altercations. Nearly every school child has witnessed violence at school firsthand. The search for answers as to why children use violence must be an ongoing conversation that challenges the myths and perceptions around the issue of school and personal violence. Intended for educators and parents, Books, Blackboards, and Bullets focuses on key issues for identification of school shooters and shootings. While explaining factors that increase the likeliness of student violence, Marcel Lebrun introduces many different perspectives that may be effective in working with troubled populations in our schools. He provides many strategies for dealing with difficult or violent youths, empowering educators to act to prevent school shootings. The book also provides checklists and assessment tools for evaluating possible dangers as well as a list of resources that educators can use in their daily work.